Clinical assessment of transoesophageal electrostimulation in first-diagnosed Type I atrial flutter - A. I. Olesin; Z. Yu. Smolin; O. A. Konovalova; A. V. Shabrov (Российский кардиологический журнал)
In total, 1283 patients with coronary heart disease and fist-diagnosed atrial flutter (AFL) episodes were followed up from 1996 to 2007. In all participants, AF was treated with transoesophageal electrocardiostimulation (TOECS). Sinus rhythm was restored in 83,48 %: in 67,3 % without any antiarrhythmic therapy (AAT), and in others - with AAT before TOECS. The best effect was observed in patients receiving amiodarone or its combination with chinidin durules. Only in 2,88 %, AFL or atrial fibrillation remained after TOECS.